Catholic moral theology in the United States: a history - Curran, Charles E. (Moral traditions series, 2008)
In this magisterial volume Charles E. Curran surveys the historical development of Catholic moral theology in the United States from its 19th century roots to the present day. He begins by tracing the development of pre-Vatican II moral theology that, with the exception of social ethics, had the limited purpose of training future confessors to know what actions are sinful and the degree of sinfulness.Curran then explores and illuminates the post-Vatican II era with chapters on the effect of the Council on the scope and substance of moral theology, the impact of Humanae vitae, Pope Paul VI's en